Projeto - Consumo consciente - Oliveira, Raquel Pereira dos Santos; Ávila, Lúcia Helena de Souza; Miotto, Jesuína Aparecida; Foresti, Nélci; Oliveira, Maria Auxiliadora de; Santos, Marlene Alves dos; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> VER PDF